2020
DOI: 10.1155/2020/5768679
|View full text |Cite
|
Sign up to set email alerts
|

Study of Factors Influencing Dry Eye in Rheumatoid Arthritis

Abstract: Purpose. The present study investigated the relationship between dry eye and the disease activity in patients with rheumatoid arthritis (RA). Methods. Patients with RA were divided by the Ocular Surface Disease Index (OSDI) into the symptomatic group (score ≥ 12) and the asymptomatic group (score < 12). By using the Disease Activity Score (DAS-28) questionnaire, they were divided into the active group (score > 2.6) and the stable group (score ≤ 2.6). In the control group, 20 healthy adults with matched s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
1
6
1
Order By: Relevance
“…A recent meta-analysis reported that DED is the most common ocular manifestation of RA with an estimated prevalence of 16%, which is slightly lower than our results [ 33 ]. Additionally, our study identified several risk factors for DED and corneal surface damages associated with RA, which were not reported in previous studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. These findings might be useful in the risk stratification and early prevention for serious ocular complications.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…A recent meta-analysis reported that DED is the most common ocular manifestation of RA with an estimated prevalence of 16%, which is slightly lower than our results [ 33 ]. Additionally, our study identified several risk factors for DED and corneal surface damages associated with RA, which were not reported in previous studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. These findings might be useful in the risk stratification and early prevention for serious ocular complications.…”
Section: Discussioncontrasting
confidence: 77%
“…The relationship between RA and DED or corneal surface damages is still not fully clarified due to some methodological limitations of previous studies, including a small sample size ( n < 1000) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], insufficient adjustment for confounders [ 17 , 18 , 19 , 20 , 22 , 23 ], and restriction to specific medical institutions [ 17 , 18 , 19 , 21 , 22 , 23 ] or populations [ 19 , 20 ]. Furthermore, relevant risk factors for corneal surface damage among patients with RA remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the biomicroscopic examination of the eye, the maximum effect is in the deep episcleral mesh and some in the superficial episcleral mesh. Treatment of scleritis requires regular therapy such as nonsteroidal anti-inflammatory drugs (NSAIDs), disease-modifying anti-rheumatic drugs (DMARDs) or corticosteroids (5,13). Posterior scleritis or scleromalacia of the cornea were not detected in the observed patient group.…”
Section: Discussionmentioning
confidence: 88%
“…Some patients report that attacks are more common in the spring or autumn. Patients suffering from nodular episcleritis typically have prolonged episodes of inflammation that are more painful than simple episcleritis (5,6,11). The use of artificial tears may be beneficial for patients with mild symptoms.…”
Section: Discussionmentioning
confidence: 99%